On the Design of a Multi-Mode Transceiver Front-End for Cellular Terminal RFICs - Hueber, Gernot; Strasser, Gernot; Maurer, Linus; Stuhlberger, Rainer; Chabrak, Karim; Hagelauer, Richard (The European Conference on Wireless Technology, 2005)
Developments aimed at the software-defined-radio (SDR) concept for cellular applications received increasing attention due to necessity of multi-mode/multi-system capable terminals for next generation cellular communication systems. This paper describes a highly reconfigurable digital-front-end (DFE) enabling multi-mode capable RF receivers for cellular applications. Its main functionality includes sample-rate-conversion, channel filtering, dynamic range control, and signal conditioning for transmission via a digital interface from RFIC to baseband IC. The described partitioning shifts some of the functionality, traditionally located in the analog-front-end (channel filtering, gain control) to the digital-front-end. The technology shift towards RF-CMOS further favors this strongly digital receiver architecture
elib2cris::1512001600,hueber2005
Keywords: CMOS integrated circuits; cellular radio; filtering theory; radiofrequency integrated circuits; software radio; wireless channels; RF-CMOS; SDR; cellular applications; cellular terminal RFIC; channel filtering; dynamic range control; multimode receive digital-front-end; sample-rate-conversion; signal conditioning; software-defined-radio; Analog integrated circuits; Application software; Baseband; Communication system control; Digital filters; Digital integrated circuits; Dynamic range; Filtering; Radio frequency; Radiofrequency integrated circuits